"Anagrelide‐induced pulmonary arterial hypertension": a rare case of drug‐induced pulmonary arterial hypertension. (1st December 2019) - Sumimoto, Keiko; Taniguchi, Yu; Matsuoka, Yoichiro; Onishi, Hiroyuki; Emoto, Noriaki; Hirata, Ken‐ichi
Abstract : Pulmonary arterial hypertension can be associated with exposure to certain drugs or toxins. However, only a few cases of drug‐induced pulmonary arterial hypertension have been previously reported. Anagrelide is an oral imidazoquinazoline agent that is prescribed for reducing elevated platelet counts in patients with myeloproliferative disorders. We report the case of a 70‐year‐old female patient who developed pulmonary arterial hypertension after taking anagrelide for the treatment of polycythemia vera. Pulmonary arterial hypertension promptly improved after the discontinuation of anagrelide. Anagrelide‐induced pulmonary arterial hypertension is a very rare disease, and our case shows that it might be reversible.